Frits Van den Berghe - Hoozee, Robert; Tahon-Vanroose, Monique; Bown-Taevernier, Sabine (Gent: Gemeentekrediet, 1983)
"Catalogus uitgegevens n.a.v. retrospectieve Frits Van den Berghe in het Museum voor Schone Kunsten te Gent"